Motywy fałszowania sprawozdań finansowych a zasady etyczne - Marek Sylwestrzak; Anna Białek-Jaworska; Krzysztof Opolski (Studia i Materiały)
This paper aims to present the motives of financial statement fraud and the impact of professional ethics on the detection and prevention of this phenomenon in business. We present the main reasons for data manipulation by management staff. The importance of professional ethics in detecting financial fraud is also described. Particular attention is paid to the factors that are most important in detecting this phenomenon. In the article, attention has been paid to the influence of whistleblowers and the role of qualitative indicators of earnings on the disclosure of the discussed procedure.